2020
DOI: 10.1155/2020/1408793
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Incidence Characteristic Evolution Based on the National Cancer Registry in Taiwan

Abstract: Introduction. Taiwan has committed itself to cancer prevention. This study investigates the impact of cancer prevention on cancer incidence in Taiwan. Objective. This study describes the secular trends and present status of cancer incidence in Taiwan during the years of 1988 to 2016. Methods. Age-standardized incidence rates (ASRs), age-specific incidence, and sex ratios for all cancers were calculated using data from the Taiwan Cancer Registry System for the years 1988 to 2016. Results and Conclusions. ASRs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 53 publications
0
22
1
Order By: Relevance
“…The incidence rate of pancreatic cancer, which has the most unfavorable prognosis and survival rate, is also increasing in Taiwan. Finally, head and neck cancers have an incidence rate ten times greater in males than in females because of the habit of chewing betel nuts [35]. In a previous study, researchers demonstrated a significant correlation between TMB and the immune response across 27 solid tumor types [1].…”
Section: Discussionmentioning
confidence: 98%
“…The incidence rate of pancreatic cancer, which has the most unfavorable prognosis and survival rate, is also increasing in Taiwan. Finally, head and neck cancers have an incidence rate ten times greater in males than in females because of the habit of chewing betel nuts [35]. In a previous study, researchers demonstrated a significant correlation between TMB and the immune response across 27 solid tumor types [1].…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, while stomach cancer is markedly prevalent in most East Asian countries, liver cancer is relatively common in Taiwan [ 43 , 44 ]. In this study, gastrointestinal cancer accounted for approximately 30%, which corresponded to the cancer epidemiology in Taiwan during the study period [ 45 ]. Unfortunately, the influence of metabolic depression on different site-specific cancers could not be studied in detail.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the TCR, with a 98.4% coverage, 93% histological verification, and 97.6% morphological verification (excluding liver), is the most important cancer registry in Taiwan. 17,18 Pancreatic cancer has an estimated coverage rate of approximately 60% for detailed cancer staging parameters in Taiwan since 2013. Admittedly, however, some limitations exist in the TCR, because some clinical factors and surgical variables may be missing or not documented in the database.…”
Section: Study Subjects In Taiwan As the Identification Setmentioning
confidence: 99%